Dinamika Resiliensi Pada Istri yang Menjadi Korban Perselingkuhan Suami - Andreas Corsini Widya Nugraha; Hanna Rahmi (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2021)
Marriage is basically building a sacred bond in which there are two persons united with a commitment to living together for all time. Every couple crave a harmonious relationship, get warmth, and eternal affection. But sometimes the desired happiness can not be realized, because of the various problems that overshadow in the world of marriage one of which is infidelity. The study used a qualitative case study approach with 2 research subjects. Something that is unique in this study is when the phenomenon of infidelity involving a husband, but the household can still be maintained. The resilience mechanism found in wives who are victims of husband infidelity is the